UJI ANTIMIKROBA EKSTRAK DAUN CIPLUKAN (Physalis angulata L.) TERHADAP PERTUMBUHAN BAKTERI Streptococcus pyogenes - Anas Fadli Wijaya; Rian Anggia Destiawan; Ayu Tri Agustin; Hartalina Mufidah; Mutia Hariani Nurjanah (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Infectious diseases caused by microbes in Indonesia are mostly due to bacterial infections. One of the bacteria responsible is Streptococcus pyogenes, which causes Acute Respiratory Infections. Treatment of infections caused by S. pyogenes mostly involves the use of antibiotics. In some cases, antibiotics often lead to resistance, necessitating alternative solutions, such as antimicrobial compounds derived from natural sources like flavonoids, one of which can be found in the extract of ground cherry leaf (Physalis angulata L.). The aim of this study is to investigate the antibacterial effects of a 70% ethanol extract of ground cherry leaves on the growth of S. pyogenes. This research is an experimental laboratory study using a post-test control group design only. The determination of antimicrobial activity was carried out using the well diffusion method. The ground cherry leaf extract, diluted with 10% DMSO, was pipetted into the wells. The positive control used chloramphenicol, while the negative control used 10% DMSO. Based on the observations, an inhibition zone was formed in the positive control with an average of 26.18 ± 1.88 mm, treatment 1 with 100% ground cherry leaf extract 16.22 ± 1.33 mm, treatment 2 with 50% ciplukan leaf extract 15.09 ± 1.01 mm, and treatment 3 with 25% ground cherry leaf extract 12.85 ± 0.87 mm.